2019
DOI: 10.1079/pavsnnr201914001
|View full text |Cite
|
Sign up to set email alerts
|

Conservation agriculture systems.

Abstract: Despite positive trajectories in global production during the last century, projected food demand and limits on our ability to further expand cropland now dictate an increase in food production by roughly 70% during the first half of the twenty-first century. Conventional systems of agriculture with their general emphasis on intensive soil disturbance, limited biodiversity, monoculture cropping and practices that mine the resource base are extractive and have resulted in slow yet demonstrably severe environmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(56 citation statements)
references
References 138 publications
1
39
0
Order By: Relevance
“…From the literature, it is also apparent that even a reduction in tillage and crop residue retention leads to enhanced chemical, microbial activity microbial biomass and enzymatic activies (Fluorescein diacetate, dehydrogenase, b Glucosidase, and Alkaline phosphatase) as compared to soils under CT (Ghosh et al, 2010;Singh et al, 2018;Choudhary et al, 2018a;Somasundaram et al, 2019;Nandan et al, 2019;Sharma et al, 2019) (Tables 3 and 4). Several authors reported that adopting CA practices including NT, crop residue retention coupled with optimum nutrient application increases SOC and total nitrogen stocks (Lal et al, 2015, Pasricha, 2017Bhattacharyya et al, 2013;2019) (Table 3). However, some authors have pointed out the conversion of CT to NT with crop residue retention did not increase SOC stocks/ sequestration (Srinivasarao et al, 2015;Dey et al, 2016).…”
Section: Effects Of Ca On Soil Chemical Properties and Plant Nutrmentioning
confidence: 99%
See 1 more Smart Citation
“…From the literature, it is also apparent that even a reduction in tillage and crop residue retention leads to enhanced chemical, microbial activity microbial biomass and enzymatic activies (Fluorescein diacetate, dehydrogenase, b Glucosidase, and Alkaline phosphatase) as compared to soils under CT (Ghosh et al, 2010;Singh et al, 2018;Choudhary et al, 2018a;Somasundaram et al, 2019;Nandan et al, 2019;Sharma et al, 2019) (Tables 3 and 4). Several authors reported that adopting CA practices including NT, crop residue retention coupled with optimum nutrient application increases SOC and total nitrogen stocks (Lal et al, 2015, Pasricha, 2017Bhattacharyya et al, 2013;2019) (Table 3). However, some authors have pointed out the conversion of CT to NT with crop residue retention did not increase SOC stocks/ sequestration (Srinivasarao et al, 2015;Dey et al, 2016).…”
Section: Effects Of Ca On Soil Chemical Properties and Plant Nutrmentioning
confidence: 99%
“…CA practices affect runoff and soil erosion processes by improving soil structure, increased infiltration, less evaporation loss, and decreased bulk density and crusting Ordoñez-Morales et al, 2019;Mitchell, 2019) (Figure 9). Soil loss could be efficiently reduced with the adoption of conservation tillage practices in SA countries ( Figure 10) where it could minimize the annual soil loss rate upto 60% (Strauss et al, 2003).…”
Section: Effects Of Ca On Reducing Soil Erosionmentioning
confidence: 99%
“…Most proposed routes to achieving such putative less resource-intensive beef envision small to medium mixed-use farms, in which cattle are a cornerstone element on account of promoting local recycling of nutrients and thus “soil building” [ 27 , 28 ]. Because on timescales up to a decade the mineral component of soil is approximately fixed, this rather vague idea addresses organic components of soil and thus biogeochemical cycling [ 29 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Vegetable production in Brazil is grounded in conventional systems involving intense tillage and the high use of agricultural inputs, which have environmental impacts such as soil erosion and contamination and the eutrophication and siltation of water resources. However, there are current agronomic techniques, such as those outlined in conservation agriculture (CA), that focus on minimal soil disturbance, permanent organic mulching on the soil surface, and crop rotation, which significantly reduce the environmental impacts (Mitchell et al 2019;Palm et al 2014).…”
Section: Introductionmentioning
confidence: 99%